American Education Statecraft and Educational Alternatives - Glinos, Peter (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
This article focuses on the Alternative Education Resource Organization (AERO), the primary hub of alternative education internationally, and its relationship to policy movements within the USA. Started by Jerry Mintz in 1989, AERO was a nexus for educational alternatives across the world including democratic, Montessori, Waldorf, Reggio Emilia, free, holistic, and virtual approaches used in public, private, and homeschools. This transnational advocacy network brought together innovative educators from Canada, the USA, Ukraine, Russia, Palestine, Israel, Guatemala, India, England, Australia, Japan, and North American Indigenous communities. AERO was invited to consult for the governments of Japan, Israel, Russia, and Ukraine in educational reforms, as well as NGOs like Dayanand Anglo Vedic in India. Moreover, the organization played a key role in sustaining and organizing the International Democratic Education Conference (IDEC).This work investigates novel primary sources drawn from AERO’s online archive of the AERO-GRAMME Newsletter and its successor, The Education Revolution magazine, the network’s main publications from 1989-2011. This study examines how, on one side, AERO's members opposed neoliberal policies that were key in increasing federal power over education within the USA such as the case of standardized testing. On the other side, AERO supported some neoliberal policies, like school choice reforms, which weakened the power of local public schools and inadvertently paved the way for the centralization of education at the federal level. At the core of my argument is the contention that AERO was a reaction against the consolidation of the education state, as can be seen by AERO’s entanglements within the USA. I analyze extensive archival material and document AERO’s connections within the United States of America to understand the paradoxes and intentionalities displayed by AERO.